Habitat preference and the effects of photoperiod on the behavior of Stichopus horrens (Echinodermata holothuroidea) juveniles - Agudia, Myrna B.; Polido, Helen Jane L.; Tavas, Michelle Kimberly L. (2012)
An organism's habitat is a crucial factor that determines its continuous growth and survival, Light, along with other environmental conditions, can also affect many aspects of the life cycle of organism, be they in their natural habitat or in culture conditions. In this study, the habitat preference of juvenile stichopus horrens (approx.1-3g) was determined by providing juvenile sea cucumbers with 3 experimental habitats, namely, coral rubble, seaweeds and sea grass, and allowing them 1 hour to choose a habitat. Results suggest that juveniles of S. horrens show no preference among the 3 habitat provided. The effect of photo period on the activity or behavior (i. e., feeding, movement and crypticity) of S. horrens juveniles was also evaluated. Three light: dark (LD) cycles representing 3 photo periods were used, namely, 0:24 LD (continuous dark), 12:12 LD, and 24:0 LD (continuous light) cycles. Observations made every 3 hours for 3 consecutive days reveal that the photo regime had a considerable effect on the activity if the juveniles. The percentage of individuals feeding, moving and exposed was significantly higher in the continuous dark treatment than those observed in the other treatments. The cryptic behavior (i.e., emerging at night while hiding during the day) of this species was also tested within a 24- hour period. Results likewise indicate that regardless of the time of day, the juveniles preferred shaded conditions where they remained active. Results from these experiments indicate that it is possible to enhance the growth rates of juvenile S. horrens by increasing the time they spend feeding through photoperiod manipulations. These results will have implications in the development of mariculture techniques for the species -- Author's Abstract.